STUDENTS' PERCEPTION OF TEACHER'S BILINGUAL LANGUAGE USE IN AN ENGLISH CLASSROOM - Nursanti, Yusi (2016)
This study, entitled "Students' Perception of Teacher's Bilingual Language Use in an English Classroom", aims to investigate the perception of students toward the use of two languages of instruction (English and Indonesian) by the teacher in an English classroom and to find out its benefits for students in learning English. This study employed qualitative approach as a basic framework of study with a case study method. The participants of this study were 50 students of 7th grade at a junior high school in Bandung Regency. The data from questionnaire were analysed based on Likert scale by Ockert (2005) for investigating students' perception and semi-structured interview by Fraenkel and Wallen (2012) for finding the benefits of teacher's bilingual language use for students in learning English. This study reveals that (1) students show their positive perceptions to the use of bilingual language by the teacher as language instruction in their English classroom; (2) there are six benefits of teacher's bilingual language use for students in learning English; making them easy to understand what the teacher explained in English lesson, feel comfortable during the class, easy to understand new vocabularies in English, help them to do exercises, help them to ask and answer something during the class, and help them to read something in English correctly. Based on the findings, some recommendations are offered to the students and teachers to be more communicative each other in order to discuss the most appropriate teacher's language use in their English classroom. The last, it is also recommended for the future researchers to investigate the contrary approach or to employ the sample from higher level of students.;---Penelitian yang berjudul "Persepsi Siswa terhadap Penggunaan Dua Bahasa oleh Guru di Kelas Bahasa Inggris" ini bertujuan untuk menginvestigasi persepsi para siswa mengenai penggunaan dua bahasa pengantar oleh guru di sebuah kelas bahasa Inggris dan mencari keuntungan-keuntungan dari penggunaan dua bahasa pengantar tersebut untuk para siswa dalam belajar bahasa Inggris. Penelitian ini menggunakan pendekatan kualitatif sebagai dasar dari penelitian dengan metode studi kasus. Partisipan dari penelitian ini adalah 50 siswa kelas 7 di sebuah Sekolah Menengah Pertama (SMP) di Kabupaten Bandung. Data yang diperoleh dari angket siswa dianalisa berdasarkan skala Likert (Ockert, 2005) untuk menginvestigasi persepsi siswa dan wawancara semi-struktur (Fraenkel and Wallen, 2012) untuk menemukan keuntungan dari penggunaan dua bahasa oleh guru bagi para siswa dalam belajar bahasa Inggris. Penelitian ini menemukan bahwa (1) para siswa menunjukkan persepsi yang positif terhadap pengunaan dua bahasa yang dilakukan oleh guru sebagai bahasa pengantar di kelas bahasa Inggris; (2) terdapat enam keuntungan dari penggunaan dua bahasa oleh guru bagi para siswa dalam belajar bahasa Inggris, diantaranya penggunaan dua bahasa oleh guru memudahkan siswa dalam memahami apa yang dijelaskan oleh guru dalam pembelajaran bahasa Inggris, membuat siswa merasa nyaman selama kelas berlangsung, membuat siswa mudah dalam memahami kosa kata baru dalam bahasa Inggris, membantu siswa dalam mengerjakan latihan, membantu siswa ketika ingin bertanya dan menjawab sesuatu selama pembelajaran, dan membantu siswa dalam membaca sesuatu dalam bahasa Inggris secara benar. Berdasarkan hasil tersebut, beberapa rekomendasi disarankan kepada para siswa dan guru untuk lebih komukatif satu sama lain dalam hal mendiskusikan penggunaan bahasa yang paling tepat digunakan oleh guru di kelas bahasa Inggris. Terakhir, rekomendasi juga ditujukan kepada para peneliti dikemudian hari untuk meneliti pendekatan lawannya atau mengikutsertakan sempel penelitian dari tingkat yang lebih tinggi.